2017
DOI: 10.1080/15257770.2016.1257808
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidine non-nucleoside analogs: A direct synthesis of a novel class of N-substituted amino and N-sulfonamide derivatives of pyrimidines

Abstract: A convenient method for the regioselective synthesis of pyrimidine non-nucleoside analogs was developed. This study reports a novel and efficient method for the synthesis of a new type of N-substituted amino methylsulfanylpyrimidines and the corresponding pyrazolo[3,4-d]pyrimidines. This series of compounds was designed through the reaction of dimethyl N-cyanodithioiminocarbonate with 2-cyano-N'-(thiophen-2-yl-, furan-2-yl- and pyridin-4-ylmethylene)acetohydrazide and N'-(2-cyanoacetyl)arylsulfonohydrazides. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…This has led to an increasing interest in benzothiazole derivatives in the area of drug design and discovery (Elgemeie et al, 2000). As a part of our research work on new syntheses of benzothiazoles as chemotherapeutic agents (Elgemeie et al, 2017), we have previously reported the synthesis of 2-arylbenzothiazoles that later found applications as anticancer agents and are presently in clinical use for various diseases (Elgemeie & Elghandour, 1990). We report here the new compound N 0 -(2-(benzo[d]thiazol-2-yl)acetyl)-4methylbenzenesulfonohydrazide (1), which was prepared by the reaction of 2-(benzo[d]thiazol-2-yl)acetohydrazide with ptoluenesulfonyl chloride in the presence of pyridine at room temperature.…”
Section: Chemical Contextmentioning
confidence: 99%
“…This has led to an increasing interest in benzothiazole derivatives in the area of drug design and discovery (Elgemeie et al, 2000). As a part of our research work on new syntheses of benzothiazoles as chemotherapeutic agents (Elgemeie et al, 2017), we have previously reported the synthesis of 2-arylbenzothiazoles that later found applications as anticancer agents and are presently in clinical use for various diseases (Elgemeie & Elghandour, 1990). We report here the new compound N 0 -(2-(benzo[d]thiazol-2-yl)acetyl)-4methylbenzenesulfonohydrazide (1), which was prepared by the reaction of 2-(benzo[d]thiazol-2-yl)acetohydrazide with ptoluenesulfonyl chloride in the presence of pyridine at room temperature.…”
Section: Chemical Contextmentioning
confidence: 99%
“…The synthesis of ketene S,S-acetals as potential starting materials for the preparation of novel classes of heterocycles has attracted much attention (Elgemeie et al 2009(Elgemeie et al , 2015. As part of a research program for preparing new classes of antimetabolites (Elgemeie et al 2016(Elgemeie et al , 2017a, we have recently reported successful approaches for syntheses of pyridine, pyrimidine and mercaptopurine analogues by the reaction of cyanoketene dithioacetals with active methylene compounds (Elgemeie et al, 2003(Elgemeie et al, , 2006(Elgemeie et al, , 2017b. In a continuation of this research, we report here a novel cyanoketene dithioacetal (1).…”
Section: Chemical Contextmentioning
confidence: 91%
“…Cyanoketene S,S-acetals and cyanoketene N,S-acetals are important synthetic intermediates (Elgemeie et al, 2015(Elgemeie et al, , 2016(Elgemeie et al, , 2017(Elgemeie et al, , 2018 that have been used as building blocks to assemble a wide range of heterocyclic compounds (Azzam et al 2017a(Azzam et al ,b, 2019; they are also of general interest in medicinal chemistry (Abu-Zaied & Elgemeie, 2017Elgemeie et al 2017c). Recently, we have reported the synthesis of various antimetabolic agents starting from cyanoketene N,S-acetals (Elgemeie et al 2006(Elgemeie et al , 2009, cyanoketene S,S-acetals (Elgemeie et al, 2003a(Elgemeie et al, , 2017d, and cyanoketene N,Nacetals (Elgemeie et al, 2003b). As a part of this programme, the reaction of (E)-ethyl 3-benzamido-2-cyano-3-(methylthio)acrylate (1) with hydrazine was investigated ( Fig.…”
Section: Structure Descriptionmentioning
confidence: 99%